Creating Dialogues : Indigenous Perceptions and Changing Forms of Leadership in Amazonia - Virtanen, Pirjo Kristiina; Veber, Hanne (Book collections on Project MUSE., 2017)
"Discusses contemporary forms of leadership in Amazonian indigenous groups. Examines the creation of indigenous leaders as political subjects in the context of contemporary state policies of democratization and exploitation of natural resources, and addresses issues of resilience and adaptation at the level of local community politics"--Provided by publisher